Records management practices of San Sebastian College-Recoletos Canlubang a plan for the establishment of an archives and records depository - Garcia, Crizell Joy P. (2013)
This study aims to analyze the current records management and recordkeeping system of SSC-RC and to propose the establishment of an archives and records depository for the college.